A study on the factor that can influence level of stress among employee: case study at PMCare Sdn Bhd / Mohd Afiq Husin and Mohd Ealizam Rasman - Husin, Mohd Afiq; Rasman, Mohd Ealizam (Faculty of Administrative Science and Policy Studies, 2011)
Work stress is now regarded by many commentators as one of the most important issues facing management in this decade. Work stress has the potential to affect the performance of all levels of staff, ranging from senior management to the young and newly employed. Stress can be defined as the body’s reaction to a change that requires a physical, mental or emotional adjustment or response. The case study will be specified where it will be conducted in one of the private company, PM CARE SDN BHD, where is located in Subang Selangor. This is the company that provide health and medical services to the clients. This company will provide a link between their clients to any health institution such as private hospital. With the challenging profession that deal with various types of people, stress might be occurs to all level of staff in this company. Therefore, the data and information will be collected from this company and being a sample to study the factor of stress in workplace.